Chemical constituents and chemotaxonomic study of Glycyrrhiza pallidiflora maxim. (February 2021) - Dai, Chen; Wang, Shuang; De Souza, Cristabelle; Li, You-Ying; Zhou, Chuang; Qiu, Reng; Xu, Xiao-Zhou; Zhou, Hong-Lei; Wu, Yi
Abstract : Phytochemical study of Glycyrrhiza pallidiflora Maxim. gave seventeen compounds, including two sterols (3 and 4 ), four triterpenes (1, 2, 5, 6 ), ten flavones (7, 9 –17 ), and one pterocarpan (8 ). The chemotaxonomic significance of G. pallidiflora was discussed, which indicated the close relationship between G. pallidiflora with other species of Glycyrrhiza . Moreover, pallidiflorin can be served as a fingerprint for G. pallidiflora, macedonic acid and echinatin can be recognized as biomarkers for Glycyrrhiza, while formononetin, afrormosin and calycosin may be typical second metabolites for Papilionoideae. Highlights: Seventeen compounds are obtained from Glycyrrhiza pallidiflora Maxim. The structures of these compounds were elucidated by spectroscopic methods and data comparison. The chemotaxonomic significance of G. pallidiflora was discussed. There are close relationships between G. pallidiflora with other species of Glycyrrhiza .